6-C-(E-phenylethenyl)naringenin induces cell growth inhibition and cytoprotective autophagy in colon cancer cells. (November 2016) - Zhao, Yueliang; Fan, Daming; Ru, Beibei; Cheng, Ka-Wing; Hu, Shuting; Zhang, Jiangwen; Li, Edmund T.S.; Wang, Mingfu
Abstract: 6- C -( E -phenylethenyl)naringenin (6-CEPN) is a small molecule found in naringenin fortified fried beef. It has been shown to suppress colon cancer cell proliferation, but the underlying mechanisms are not fully understood. Here we demonstrate that 6-CEPN suppresses tumour cell proliferation through cell cycle arrest in G1 phase, induces necrotic cell death and autophagy in colon cancer cells. Blockade of autophagy by knockdown of the essential autophagy proteins, Atg7 or beclin-1, resulted in aggravated cell death in response to 6-CEPN treatment. In addition, genome-wide transcriptome expression profiling by RNA-sequencing revealed that 6-CEPN-mediated gene expression pattern was extremely similar to the transcriptome response induced by a RAS inhibitor salirasib (farnesylthiosalicylic acid [FTS; salirasib]). Subsequent molecular biological and biochemical experiments demonstrated that 6-CEPN indeed strongly inhibited RAS activation, leading to the inhibition of the downstream effector pathways c-Raf/mitogen-activated protein kinase (MEK)/extracellular signal-regulated kinase kinase and phosphoinositide 3-kinase/AKT/mammalian target of rapamycin. More importantly, our computational molecular docking data showed that 6-CEPN could bind to the active site of isoprenylcysteine carboxyl methyltransferase (Icmt), a critical enzyme for the activation of RAS. Icmt activity assay showed that 6-CEPN inhibited its activity significantly. Knockdown of Icmt by siRNA attenuated 6-CEPN-mediated autophagy and cell death. The present study demonstrates that 6-CEPN induces cell growth inhibition and cytoprotective autophagy in colon cancer cells, at least in part, though inhibition of the Icmt/RAS signalling pathways. Highlights: 6- C -( E -phenylethenyl)naringenin (6-CEPN) inhibits cell proliferation and induces necrosis in human colon cancer cells. 6-CEPN-induced autophagy protects colon cancer cells from death. 6-CEPN inhibits RAS activation and its downstream effector pathways. 6-CEPN could bind to the active site of isoprenylcysteine carboxyl methyltransferase and inhibit its activity.